In-Vitro Antibacterial Activity of Plantago Lanceolata Against Some Selected Standard Pathogenic Bacterial - Kassaw, Eshetie; Yohannes, Tilahun; Bizualem, Endalkachew (The International Journal of Biotechnology, 2018)
The leaves of Plantago lanceolata have been used for centuries to treat diseases. Currently there is an increasing incidence of multiple antibiotic resistances in microorganisms which is a major threat. Widespread overuse of antibiotics is one led to increasing clinical resistance of previously sensitive microorganisms and the emergence of previously uncommon infections. Thus all these calls for an urgent need to search new, effective and safe anti-bacterial agents. The objective of this study was to determine antibacterial potentials of extracts of P. lanceolata against standard pathogens bacteria. Active antibacterial compounds were extracted using three solvents. The antibacterial sensitivity activities of crude extracts were determined using agar well diffusion assay. MIC and MBC of each crude extracts were also determined using broth dilution method. The test showed various degrees of antibacterial activity towards each standard pathogenic microorganism with mean zone of inhibition ranges up to 18±2mm against S. typhi. The plant extract was showed as low 3±1mm to high 18±2mm diameter inhibition zone. Chloroform extract have the least inhibition zone while the ethanol have highest inhibition zone. The extract value of MIC was showed at the ranges of 12.5mg to 50mg while the MBC were showed at the range of 25mg to 50mg. The result of this study showed that leaves of P. lanceolata have considerable antibacterial potential. The claimed efficacy could be attributable to antibacterial activity of its components but its mode of action is unclear.